De la fabrication de « pots » à la création d’un goût national : le cas Wedgwood - Laurence Machet (Revue Française de Civilisation Britannique)
This article examines the role of Josiah Wedgwood, the famous potter, in the shaping and spreading of a new, typically British taste. By developing innovative ceramic substances, producing portrait-medallions and manufacturing the Frog Service, Wedgwood was instrumental in moulding the new image of Britain. But he also managed to modify the status of both his own production and that of the nation’s budding industry.